PENGABDIAN KEPADA MASYARAKAT OLEH JURUSAN BAHASA DAN SASTRA ARAB UIN ALAUDDIN MAKASSAR: MEMBANGUN JEMBATAN KEILMUAN BAHASA DAN SASTRA (DI PONDOK PESANTREN AL-IKHLASH ADDARY DDI TAKKALASI KABUPATEN BARRU) - Khaerun Nisa Nuur; Baso Pallawagau; Mohamad Harjum; Muhammad Saleh; Anwar Abd Rahman; Muhsin; Husni Mubarak (JURNAL KHAZANAH PENGABDIAN, 2024)
Community service is the main principle upheld by higher education institutions in fighting for the empowerment and advancement of society. This paper aims to illustrate the important role of the Department of Arabic Language and Literature at UIN Alauddin Makassar in implementing community service programs, with a case study at Pondok Pesantren al-Ikhlash Addary DDI Takkalasi, Barru Regency. Through a qualitative approach and direct observation, this article discusses the various service activities carried out by the department in improving the quality of life and empowering the local community. The results show that the role of the Department of Arabic Language and Literature is very significant in making a positive contribution to the pesantren and the surrounding community, especially in terms of scientific development and cultural maintenance.